PENYUSUNAN RENCANA PROGRAM KEMITRAAN KONSERVASI MENGGUNAKAN METODE PENDEKATAN PARTICIPATORY CONSERVATION PLAN (PCP) DI TAMAN WISATA ALAM PELAIHARI - Saputra, Debi Imam; Kissinger, Kissinger; Satriadi, Trisnu; Aryadi, Mahrus (Lambung Mangkurat University-Indonesia, 2024)
This study aims to determine the preparation of conservation partnership program planning in TWA Pelaihari. The method used in this study is descriptive with a qualitative approach which is described in a descriptive form, by describing the preparation of the conservation partnership program planning obtained from observations, interviews, literature studies, documentation and FGD (Focus Group Discussion). Data analysis used Participatory Conservation Plan (PCP) analysis. The results of the analysis of factors/activities that affect the system in the Pelaihari TWA area in the first rank (I) are occupied by tree logging activities where the disturbance value (C) is 61, a percentage of 35.9% where tree logging activities carried out by the community are very widespread, the second rank (II) is occupied by the waste factor where the disturbance value (C) is 40, a percentage of 23.5%, this is due to the presence of visitors, both local and visitors from outside, who bring garbage into the Pelaihari TWA area and the third rank (III) is occupied by natural factors where the disturbance value (C) is 25 with a percentage of 14.7%, this is due to the influence of the tides and seawater which results in damage to the ecosystem in the Pelaihari TWA area. Preparation of a conservation partnership plan based on a participatory conservation planning process involving elements of the community, village government and the South Kalimantan BKSDA where the strategy formulated supports the success of the conservation partnership program.